Mammalian Diversity on Different Habitat Types in Muara Bungo, Jambi - Agus P Kartono; Ibnu Maryanto; Martua H Sinaga (Department of Forest Resources Conservation and Ecotourism - IPB University, 2000)
The study of mammalian diversity was done at Pasir Mayang, Pancuran Gading and Kuamang Kuning - Muara Bungo, Jambi in six different vegetation types, namely primary forest, logged over area or secondary forest, Parasarienthes falcataria plantation, rubber plantation, and jungle rubber forest; each of it was contiguous each other, and the last area was grass land-cassava type area, which were laid on about 10 km of South East to other types. To predict the effect of different habitat types on mammals diversity we used the Linetransect methods. By using the reconnaissance methods, species and number of individual for each species was recorded. The results showed that there were 20 species of mammals at the six habitat types. The highest diversity was on logged overlsecondary forest and the lowest was grass land-cassava area. Based on species richness indices, it was indicated that jungle rubber and logged over area had 10.OO?higher than primary forest. The equality of rank community index between primary forest and logged over area were 55.56%. Based on cluster analysis, there were three groups of habitats used by mammalians. The first group was jungle rubber; second were rubber plantation, cassava-grass land area, and Parasarienthes falcataria plantation; and third was primary-secondary/logged over area Keywords : mammalian, forest plantation, microbiogeography, habitat, Hylobates sp.